2014
DOI: 10.1017/s0954579414000017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal parenting predicts infant biobehavioral regulation among women with a history of childhood maltreatment

Abstract: Early biobehavioral regulation, a major influence of later adaptation, develops through dyadic interactions with caregivers. Thus, identification of maternal characteristics that can ameliorate or exacerbate infants’ innate vulnerabilities is key for infant well-being and long-term healthy development. The present study evaluated the influence of maternal parenting, postpartum psychopathology, history of childhood maltreatment, and demographic risk on infant behavioral and physiological (i.e., salivary cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 91 publications
(125 reference statements)
2
82
2
Order By: Relevance
“…A variety of previous studies have shown that depressed mothers are less emotionally available and thus, respond less sensitively and more intrusively or hostilely in dyadic interactions with their offspring [3,4,5]. The emotional quality of the mother-child relationship during infancy and early childhood is thought to foster the development of secure child attachment, which has been shown to positively affect children's emotion and stress regulation skills [6,7,8]. Thus, children of depressed mothers constitute a high-risk group for later development of reduced socioemotional competencies and increased psychopathology [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of previous studies have shown that depressed mothers are less emotionally available and thus, respond less sensitively and more intrusively or hostilely in dyadic interactions with their offspring [3,4,5]. The emotional quality of the mother-child relationship during infancy and early childhood is thought to foster the development of secure child attachment, which has been shown to positively affect children's emotion and stress regulation skills [6,7,8]. Thus, children of depressed mothers constitute a high-risk group for later development of reduced socioemotional competencies and increased psychopathology [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers with histories of childhood physical abuse, but not sexual abuse, had increased risk for postpartum SI. In terms of behavioral disruptions, women with CM histories have greater difficulties when interacting with their infants (Levendosky and Graham-Bermann, 2001) which impacts child development (Martinez-Torteya, et al, 2014). Investigations incorporating more comprehensive assessment of CM including multiple types of abuse and neglect, and the severity of maltreatment with validated measures may further elucidate relationships between distal trauma exposure (e.g., abuse and neglect), postpartum functioning, and SI, and is a principle aim of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The SFP has been widely utilized both in healthy mothers and mothers with depression [19,21], and a smaller number of studies with mothers with PTSD [18,22], and overall is a valid measure to tap into interactive affective exchanges [23]. Further, research has documented that infant and mother behavior varies by type of interactive task and that more challenging tasks tend to pull for more individual differences in behavior as well as more negative maternal behaviors (24).…”
Section: Introductionmentioning
confidence: 99%